The Nynas Nitro Libra Oil Testing as an Isolator on the 150 kV Transformer Using Colour, Water Content, and Breakdown Voltage Testing Method in Bantul Substation - Ardianta, Dimas Septe; Syahputra, Ramadoni; Mustar, Muhamad Yusvin (Journal of Electrical Technology UMY, 2018)
In the system of electricity power, either thermal or electric failure often takes place. In order to prevent such failure, isolator testing towards the power transformer is needed. A mineral oil Nynas Nitro Libra was used as the research subject, in which it was compared to the other oil types, involving new oil, in-use oil, and used crude oil. The method used was testing throughout the colour, water content, and breakdown voltage. Colour testing was conducted by comparing between used oil and typical oil, whereas water content was conducted by mixing chemical ingredients which were Solvent Xylol and toluene, followed by 100Â°C heating process within 3 hours and condenser cooling down until the moisture dropped down the trap, finished by 6 times breakdown voltage test through environment temperature. The testing result shows that crude oil indicates D 8,0 (black colour), with moisture content TRACE (0,2%) which is 4 ppm. The value of 6-time breakdown voltage test in the temperature of 22Â°C indicates: 09.4 KV, 09.1 kV, 09.2 kV, 09.6 kV, 09.5 kV, 12.0 kV with dielectric power 3.92 kV/mm.